2021
DOI: 10.3389/fped.2021.625377
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Children With Kawasaki Disease-Like Signs in COVID-19 Pandemic: A Systematic Review

Abstract: Recent studies have shown that several children diagnosed with COVID-19 have developed Kawasaki Disease (KD)-like symptoms. This systematic review aims to assess the demographic, laboratory, and clinical characteristics of children with KD-like syndrome during the COVID-19 pandemic and evaluate efficacy of treatments and patients' outcome. A comprehensive search was carried out systematically through PubMed, Scopus, and Web of Science (WoS), medRxiv, and bioRxiv by two reviewers independently for all studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…However, high inappropriate prescribing will increase antimicrobial resistance (AMR) rates, increasing morbidity, mortality and costs [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], with high rates of AMR already a concern in Bangladesh [ 33 , 34 , 35 , 36 ]. Children with COVID-19 can also develop Kawasaki Disease (KD)-like symptoms/hyperinflammatory syndromes [ 8 , 37 , 38 , 39 ] as well as experience leucopoenia with marked lymphopenia, hyponatremia, hypoalbuminemia, gastrointestinal and respiratory changes [ 37 ], potentially increasing ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…However, high inappropriate prescribing will increase antimicrobial resistance (AMR) rates, increasing morbidity, mortality and costs [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], with high rates of AMR already a concern in Bangladesh [ 33 , 34 , 35 , 36 ]. Children with COVID-19 can also develop Kawasaki Disease (KD)-like symptoms/hyperinflammatory syndromes [ 8 , 37 , 38 , 39 ] as well as experience leucopoenia with marked lymphopenia, hyponatremia, hypoalbuminemia, gastrointestinal and respiratory changes [ 37 ], potentially increasing ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…We see though that children diagnosed with COVID-19 do develop Kawasaki Disease (KD)like symptoms/ hyperinflammatory syndromes 41,81-83 , which is reflected by higher C-reactive protein and erythrocyte sedimentation rates and children experiencing leucopoenia with marked lymphopenia, hypoalbuminemia, and hyponatremia along with gastrointestinal changes, abnormal electrocardiogram (ECG) and respiratory changes 81 , which can result in the need for intensive care 81 . This is important as we know from research with adults with COVID-19 in ICUs in Bangladesh that over 50% died whilst in ICU 84 .…”
Section: Introductionmentioning
confidence: 99%
“…Our meta‐analysis showed that patients in the PHICs group had a slight male preponderance, as seen in previous studies, for all 3 conditions. However, the prevalence of PHICs with younger age was less conclusive; as patients in the PHICs group were reported to be younger, however, this group had a higher mean age [28–31] upon exclusion of Feldstein et al. [8] study.…”
Section: Discussionmentioning
confidence: 99%